How Islamic Economics View on Ecology? - Muhammad Anis; Irham Zaki (AFEBI Islamic Finance and Economic Review, 2019)
As ecological problems become more apparent, public awareness of their dependence on nature is increasing. This then raises the urge to care about ecological issues. In line with this, there was also a movement that blended ecological issues with religious issues. So, there arose a scientific interest in studying religion in relation to ecology, including in Islam. In this case the discussion will focus on how Islamic economic views about ecology. By using qualitative methods, the discussion is focused on getting an overview of the Islamic economic view of ecology. Islamic economic bases its value on the concept of tauhid, so it views ecology as a unified relationship between God, man and nature. Al-Quran, as the main source of sharia values, explains a lot about the nature and ecological crises that can occur if humans do damage. Islamic economics is full of moral values, in exploring nature, human must uphold the prevailing moral values and pay attention to the principles of maslahah and maqashid sharia.